A circularly polarized luminescent quantum dot material and its preparation method and application

By combining quantum dots with chiral two-dimensional nanosheets, the problem of poor performance of circularly polarized luminescent quantum dot materials in the water phase in the prior art is solved, efficient emission of CPL and good biocompatibility are achieved, and the possibility of biomedical applications is expanded.

CN118813240BActive Publication Date: 2025-04-15NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410878143.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-04-15
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

In the prior art, circularly polarized luminescent quantum dot materials have poor performance in the aqueous phase to emit CPL and the production process is complex, which limits its development in biomedical applications.

Method used

By combining quantum dots with chiral two-dimensional nanosheets, the strong chiral field of the chiral assembly is used to induce adsorption of quantum dots, and efficient emission of CPL in the aqueous phase is achieved.

Benefits of technology

It has achieved efficient emission of left/right circularly polarized light in the aqueous phase, the material is simple to prepare and has good biocompatibility, and has expanded the application field of circularly polarized luminescent quantum dot materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118813240B_ABST
    Figure CN118813240B_ABST
Patent Text Reader

Abstract

The present invention provides a circularly polarized luminescent quantum dot material and a preparation method and application thereof; the circularly polarized luminescent quantum dot material is composed of a luminescent subject and a chiral assembly; the luminescent subject is adsorbed on the chiral assembly through chemical bonding; the luminescent subject is a quantum dot; the circularly polarized luminescent quantum dot material can emit left / right circularly polarized light in an aqueous phase. By adopting the technical solution of the present invention, a circularly polarized luminescent quantum dot material is prepared by combining quantum dots with a two-dimensional chiral nanoassembly, and this circularly polarized luminescent system is applicable to a variety of luminescent subject quantum dots. The preparation method of the circularly polarized luminescent quantum dot material is simple, can be well dispersed in an aqueous phase system, and has good thermal stability and biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic luminescent materials, and in particular relates to a circularly polarized luminescent quantum dot material and a preparation method and application thereof. Background Art

[0002] Chiral optical materials with circularly polarized luminescence (CPL) properties have attracted much attention due to their unique application value in the fields of three-dimensional display, optical communication, information encryption and biological applications. Especially in biological applications, materials with CPL characteristics have unique advantages because their luminescence characteristics are easy to distinguish and have high sensitivity. Quantum dots have excellent fluorescence properties such as wide and continuous excitation spectrum, narrow and symmetrical emission spectrum, tunable color, high photochemical stability, and long fluorescence lifetime. They are ideal fluorescent probes. So far, many quantum dot materials with CPL characteristics have been developed and have shown great potential in biological application scenarios.

[0003] Most of the circularly polarized luminescent quantum dot materials that have been developed so far are based on the modification and expansion of chiral luminescent structures. Due to the small number of feasible structures and the complex synthesis process, they have certain limitations. Chiral assemblies have attracted more and more attention due to their simple preparation methods, excellent CPL performance, and good universality. For example, circularly polarized luminescent quantum dots with high glum (luminescence asymmetry factor) values ​​can be achieved by co-assembly of liquid crystals and quantum dots. In addition, various chiral assembly matrices with CPL properties continue to emerge, including cellulose nanocrystals, organic gels, etc. However, most of the existing chiral assemblies are of inappropriate size, and many cannot be well dispersed in water. These inherent characteristics limit their biocompatibility. For example, Chinese invention patent CN1 16463120A discloses a method for preparing a room temperature circularly polarized phosphorescent material based on carbon quantum dots-nucleobase derivatives. By co-assembling carbon quantum dots and nucleobase derivatives, a material with room temperature circularly polarized phosphorescent properties is formed, but this material is limited to the circular polarization development of carbon quantum dots and does not have universality. Chinese invention patent CN1 15505149A discloses a circularly polarized luminescent material and a preparation method thereof, which uses a method of inducing anisotropy of dielectric constant in the environment to make the luminescent material form an adjustable circularly polarized luminescent material. It has universal applicability to organic and inorganic luminescent materials, but this material is limited to a thin film state and cannot achieve CPL emission in the aqueous phase.

[0004] Therefore, developing a simple and universal method to achieve efficient CPL emission in water phase and prepare circularly polarized luminescent quantum dots with submicron size is of great significance for the application of circularly polarized luminescent quantum dot materials in biomedicine. Based on the above technical problems, the present invention provides a novel circularly polarized luminescent quantum dot assembly system, which utilizes the assembly of quantum dots and chiral two-dimensional chiral nanosheets to achieve the CPL characteristics of the water phase system. Summary of the invention

[0005] The purpose of the present invention is to overcome the technical problems in the prior art that the construction of the circularly polarized luminescent quantum dot system is complicated, and the chiral assembly of the circularly polarized luminescent quantum dot material is limited in application due to inappropriate matrix size and poor dispersibility in water, and to provide a circularly polarized luminescent quantum dot material and a preparation method and application thereof to solve the problems in the prior art.

[0006] To achieve the above object, the present invention provides a circularly polarized luminescent quantum dot material, which is composed of a luminescent main body and a chiral assembly; the luminescent main body is adsorbed on the chiral assembly through chemical bonding.

[0007] Preferably, the light-emitting body is a quantum dot.

[0008] Preferably, the circularly polarized luminescent quantum dot material can emit left / right circularly polarized light in an aqueous phase.

[0009] Preferably, the chiral assembly is a two-dimensional chiral nanosheet, and the strong chiral field it possesses can induce the luminescent host adsorbed on the surface of the chiral assembly to emit circularly polarized light.

[0010] Preferably, the chiral assembly is obtained by self-assembly of gold thiol sheets (Au(I)-MPA) and cyclohexanediamine.

[0011] Preferably, the quantum dots are adsorbed on the surface of the chiral assembly through hydrogen bonding.

[0012] Preferably, the quantum dots are carbon quantum dots or graphene quantum dots.

[0013] More preferably, the graphene quantum dots are boron-doped graphene quantum dots or amination-modified graphene quantum dots.

[0014] As another object, the present invention also provides a method for preparing the above-mentioned circularly polarized luminescent quantum dot material, wherein the circularly polarized luminescent quantum dot material is obtained by mixing a chiral two-dimensional nanoassembly and a quantum dot solution; the chiral assembly is obtained by self-assembly of a gold thiol sheet (Au(I)-MPA) and cyclohexanediamine.

[0015] Specifically, the method for preparing the circularly polarized luminescent quantum dot material comprises the following steps:

[0016] S1. Providing a two-dimensional chiral nanoassembly;

[0017] The sodium salt of 3-mercaptopropionic acid is added to a boiling mixed aqueous solution of chloroauric acid and alkali solution to obtain a colloidal solution of gold (I)-mercaptopropionic acid (Au (I)-MPA) two-dimensional nanoassembly by a solvothermal synthesis method; the colloidal solution is post-treated to obtain a gold mercaptan two-dimensional nanoassembly solution;

[0018] S2. providing an aqueous solution of a chiral two-dimensional nanoassembly;

[0019] The gold mercaptan two-dimensional nanoassembly solution is added into the cyclohexanediamine aqueous solution and mixed to obtain a chiral two-dimensional nanoassembly aqueous solution through self-assembly;

[0020] S3. Preparation of circularly polarized luminescent quantum dot materials;

[0021] The circularly polarized luminescent quantum dot material is obtained by mixing the chiral two-dimensional nanoassembly aqueous solution and the quantum dot aqueous solution.

[0022] Preferably, in S1, the reaction time of the solvent thermal synthesis method is 5 to 20 minutes.

[0023] More preferably, the alkali solution is a sodium hydroxide solution;

[0024] More preferably, the molar ratio of chloroauric acid to 3-mercaptopropionic acid monosodium salt is in the range of 1:3 to 1:5.

[0025] More preferably, the post-treatment includes centrifugation and purification; the centrifugation includes centrifugation at a speed of 8000 r / s for 10 to 20 min;

[0026] Preferably, the concentration range of the gold thiol two-dimensional nanoassembly solution is 0.8×10 -3 M~1.2×10 -3 M.

[0027] Preferably, in S2, the concentration of cyclohexanediamine in the aqueous solution of the chiral two-dimensional nanoassembly is 4×10 -4 M; the concentration of the chiral two-dimensional nanoassembly is 3.8×10 -4 M.

[0028] Preferably, in S3, the concentration of the quantum dot aqueous solution is 0.26 mg / mL to 1.20 mg / mL.

[0029] Preferably, in the circularly polarized luminescent quantum dot material, the added volume ratio of the chiral two-dimensional nanoassembly and the quantum dots is 1:1.

[0030] The present invention provides a novel circularly polarized luminescent quantum dot assembly system, which realizes the CPL characteristics of the aqueous system by assembling quantum dots and chiral two-dimensional chiral nanosheets; due to the differential absorption of left-handed / right-handed CPL by the chiral two-dimensional nanoassembly, the quantum dots adsorbed on the surface of the chiral nanoassembly through hydrogen bond interaction show obvious CPL characteristics. Using quantum dots as the main research object, the optimal concentration ratio of the system was explored, and a perfect mirror CPL signal was obtained, with the highest g value of 5.07×10 -3 Furthermore, CPL signals can be successfully induced using boron-doped graphene, carbon quantum dots or amino-modified graphene quantum dots systems.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The technical solution of the present invention is used to prepare a circularly polarized luminescent quantum dot material by combining quantum dots with two-dimensional chiral nanoassemblies. The circularly polarized luminescent system is suitable for a variety of luminescent host quantum dots. The circularly polarized luminescent quantum dot material has a simple preparation method and can be well dispersed in an aqueous system, and therefore has not only good hydrophilicity but also good biocompatibility.

[0033] 2. By adopting the technical solution of the present invention, the method for constructing a circularly polarized luminescent quantum dot system is simple, and the circularly polarized luminescent quantum dot system has universal applicability, especially its good biocompatibility, which expands the application field of circularly polarized luminescent quantum dot materials.

[0034] 3. The method for preparing quantum dot materials with circularly polarized luminescence properties provided by the technical solution of the present invention has the characteristics of being simple and easy to operate, having a wide range of applications, good dispersibility in water, and good biocompatibility. Moreover, it has broad application prospects in biological imaging, cell probes, sensors, drug treatment and delivery, etc.

[0035] 4. The circularly polarized luminescent quantum dot material obtained by combining quantum dots with two-dimensional chiral nanoassemblies in the present invention is suitable for a variety of luminescent host quantum dots, and can emit left / right circularly polarized light in the water phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the preparation process of the chiral two-dimensional nanoassembly provided by the present invention.

[0037] Figure 2a and Figure 2b They are TEM images of the two-dimensional chiral nanoassembly in Example 1 of the present invention respectively.

[0038] Figure 2c and Figure 2dThey are respectively schematic diagrams of optical absorption characterization of the two-dimensional chiral nanoassembly in Example 1 of the present invention.

[0039] Figure 3a and Figure 3b They are respectively TEM images of the circularly polarized luminescent quantum dot material in Example 1 of the present invention.

[0040] Figure 3c , Figure 3d , Figure 3e and Figure 3f They are respectively schematic diagrams of characterizing the circularly polarized luminescence of the circularly polarized luminescent quantum dot material in Example 1 of the present invention.

[0041] Figure 4a and Figure 4b They are respectively schematic diagrams of characterizing the circularly polarized luminescence of circularly polarized luminescent quantum dots prepared using carbon quantum dots in Example 2 of the present invention.

[0042] Figure 4c and Figure 4d They are respectively schematic diagrams of characterization of circularly polarized luminescence of circularly polarized luminescent quantum dots prepared by amino-treated graphene quantum dots in Example 3 of the present invention.

[0043] Figure 5a and Figure 5b They are schematic diagrams for characterizing the luminescence performance of circularly polarized luminescent quantum dots prepared by using boron-doped graphene quantum dots with different concentrations in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. In order to describe concisely, it is impossible for this specification to describe in detail all the features of the actual implementation method. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise defined, the technical terms or scientific terms used in this specification should be known to those in the technical field described in this application.

[0045] The invention discloses a construction method and application of a circularly polarized luminescent quantum dot material, wherein the circularly polarized luminescent quantum dot comprises a luminescent subject and a chiral assembly. The chiral assembly is a chiral two-dimensional nanoassembly obtained by self-assembly of a gold thiol sheet (Au(I)-MPA) and cyclohexanediamine to achieve chiral sensing. The luminescent subject is a quantum dot, which is adsorbed on the chiral two-dimensional nanoassembly through hydrogen bond interactions. The chiral two-dimensional nanoassembly provided by the invention has a strong chiral field that can induce the quantum dot system to emit circularly polarized light.

[0046] The circularly polarized luminescent quantum dot material described in the present invention can be prepared by the following steps: (1) preparation of a two-dimensional chiral nanoassembly; (2) preparation of a circularly polarized luminescent quantum dot material. The preparation steps are as follows:

[0047] See also Figure 1 The preparation steps of the chiral two-dimensional nanoassembly include: adding 3-mercaptopropionic acid monosodium salt to a boiling mixed aqueous solution of chloroauric acid and sodium hydroxide, and obtaining a gold (I)-mercaptopropionic acid (Au (I)-MPA) two-dimensional nanoassembly colloid by a solvothermal synthesis method. After centrifuging and purifying the colloidal solution, it is mixed with an aqueous solution of cyclohexanediamine to obtain a chiral two-dimensional nanoassembly; further, the obtained chiral two-dimensional nanoassembly is mixed with a quantum dot solution of a suitable concentration in a certain proportion to obtain a mixed aqueous solution, which is a circularly polarized quantum dot luminescent material.

[0048] The preparation method of the circularly polarized luminescent quantum dot system provided based on the above technical solution has the characteristics of simple and easy operation, wide application range, good dispersibility in water, good biocompatibility, etc. Moreover, it has broad application prospects in biological imaging, cell probes, sensors, drug treatment and delivery, etc.

[0049] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0050] The technical solution of the present invention is described in detail below through specific embodiments.

[0051] Example 1

[0052] This embodiment provides a method for preparing a circularly polarized luminescent quantum dot material, and the specific steps include:

[0053] 1. Provide a chiral two-dimensional nanoassembly, the preparation method of which comprises:

[0054] (1) Preparation of gold thiol two-dimensional nanoassemblies (Au(I)-MPA):

[0055] Dissolve 1 g of chloroauric acid in 50 mL of water to obtain a 0.05 M chloroauric acid solution.

[0056] Take 400 μL of chloroauric acid solution and 20 mL of pure water and place them in a conical flask. Heat them on a hot plate until boiling.

[0057] Then, 1.6 mL of a mixed solution of 3-mercaptopropionic acid monosodium salt (50 mmol) and 1.2 mL of NaOH (100 mmol) was injected into the boiling solution, and the mixture was heated for 10 minutes and then cooled to room temperature naturally to obtain a blue-white colloidal solution.

[0058] The colloidal solution was centrifuged at 8000 r / s for 20 minutes, the supernatant was removed, and water with a volume of three-quarters of the original colloidal solution was added to obtain the gold thiol two-dimensional nanoassembly (Au(I)-MPA) (0.93×10 -3 M).

[0059] (2) Preparation of two-dimensional chiral nanoassemblies

[0060] Add gold thiol two-dimensional nanoassemblies (0.93×10 -3 M), pure water, cyclohexanediamine solution (1×10 -3 M) to form a mixed system, in which the final concentrations of cyclohexanediamine and gold mercaptan two-dimensional nanoassemblies were 4×10 -4 M and 3.8×10 -4 M.

[0061] 2. Preparation of circularly polarized luminescent quantum dot materials

[0062] First, a boron-doped graphene quantum dot solution (commercially available, Nanjing Xianfeng Nanomaterial Technology Co., Ltd.) was diluted to a series of concentration gradients for use (respectively 0.26 mg / mL, 0.4 mg / mL, 0.54 mg / mL, 0.66 mg / mL, 1.0 mg / mL, 1.20 mg / mL). In this step, the concentration of quantum dots in the solution can be adjusted by changing the volume of purchased quantum dots added and the proportion of pure water added.

[0063] Subsequently, the two-dimensional chiral nanoassembly (3.8×10 -4 M) and the above series of quantum dot solutions with concentration gradients are mixed evenly to obtain the mixed aqueous solution of the circularly polarized luminescent quantum dot material.

[0064] The concentration of quantum dots in the final system is in the range of 0.13 mg / mL to 0.60 mg / mL.

[0065] Example 2

[0066] The only difference between this embodiment and embodiment 1 is that in step 2, the quantum dots used are carbon quantum dots (commercially available, Suzhou Xingshuo Nanotechnology Co., Ltd.), and the concentration of the diluted carbon quantum dot solution is 0.58 mg / mL.

[0067] Example 3

[0068] The only difference between this embodiment and embodiment 1 is that in step 2, the quantum dots used are amino graphene quantum dots (commercially available, Nanjing Xianfeng Nanomaterial Technology Co., Ltd.), and the concentration of the amino graphene quantum dot solution after dilution is 0.54 mg / mL.

[0069] Comparative Example 1

[0070] The only difference between this comparative example and Example 1 is that in step 2, the final concentration of boron-doped graphene quantum dots is 0.26 mg / mL; 0.40 mg / mL; 0.57 mg / mL; 0.66 mg / mL; 1.00 mg / mL; 1.20 mg / mL.

[0071] Performance characterization:

[0072] See also Figure 2a and Figure 2b They are TEM images of the two-dimensional chiral nanoassembly in Example 1. As can be seen from the figures, the chiral assembly is in the form of a two-dimensional spindle-shaped sheet and has a self-supporting two-dimensional layered nanostructure.

[0073] See also Figure 2c and Figure 2d They are optical absorption characterizations of the two-dimensional chiral nanoassembly in Example 1. It can be seen from the figure that the chiral assembly has strong circular dichroism and ultraviolet absorption in the 380nm-440nm band, and the cyclohexanediamine and gold mercaptan assemblies alone have no circular dichroism absorption.

[0074] See also Figure 3a and Figure 3b They are TEM images of the circularly polarized luminescent quantum dot material in Example 1. It can be seen from the figure that the morphology of the chiral assembly has not changed before and after the addition of quantum dots, and it still presents a two-dimensional shuttle-shaped flake, proving that the addition of quantum dots has no effect on the morphology of the assembly.

[0075] See also Figure 3c and Figure 3f They are respectively the circularly polarized luminescence characterizations of the circularly polarized luminescent quantum dot materials in Example 1. As can be seen from the figure, after the two chiral assemblies of R configuration and S configuration are co-assembled with quantum dots, they show perfect mirror-image CPL signals, and the circular dichroism and ultraviolet absorption of the two configuration systems are consistent.

[0076] See also Figure 4aand Figure 4b They are respectively the circularly polarized luminescence characterizations of the circularly polarized luminescent quantum dots prepared using carbon quantum dots in Example 2. As can be seen from the figures, the carbon quantum dot system has CPL signals and CD signals, proving that the circularly polarized luminescence induction of the system is successful.

[0077] See also Figure 4c and Figure 4d They are respectively the circularly polarized luminescence characterizations of the circularly polarized luminescent quantum dots prepared by amino-treated graphene quantum dots in Example 3 of the present invention. As can be seen from the figures, the amino-treated quantum dot system has CPL signals and CD signals, proving that the circularly polarized luminescence induction of the system is successful.

[0078] See also Figure 5a and Figure 5b They are respectively the circularly polarized luminescence characterizations of circularly polarized luminescent quantum dots prepared by using boron-doped graphene quantum dots with different concentrations in Comparative Example 1 of the present invention. It can be seen from the figure that when quantum dots of different concentrations are added, the photoluminescence quantum yield (PLQY) of the system increases with the increase of quantum dot concentration. However, when the quantum dot concentration increases to above 0.30 mg / mL, the system |glum| value remains similar, proving that the system-induced circularly polarized light is saturated.

[0079] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or capable of achieving the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.

Claims

1. A circularly polarized luminescent quantum dot material, comprising a luminescent main body and a chiral assembly; the luminescent main body is adsorbed on the chiral assembly through chemical bonding; The light-emitting body is a quantum dot; The quantum dots are carbon quantum dots or graphene quantum dots; The circularly polarized luminescent quantum dot material can emit left / right circularly polarized light in the water phase; The chiral assembly is obtained by self-assembly of gold thiol sheets and cyclohexanediamine; The strong chiral field of the chiral assembly can induce the light-emitting host adsorbed on the surface of the chiral assembly to emit circularly polarized light.

2. The circularly polarized luminescent quantum dot material according to claim 1, characterized in that: The quantum dots are adsorbed on the surface of the chiral assembly through hydrogen bonding.

3. The circularly polarized luminescent quantum dot material according to claim 1, characterized in that: The graphene quantum dots are boron-doped graphene quantum dots or amino-doped graphene quantum dots.

4. The method for preparing a circularly polarized luminescent quantum dot material according to any one of claims 1 to 3, characterized in that: The circularly polarized luminescent quantum dot material is obtained by mixing a chiral two-dimensional nanoassembly and a quantum dot solution; the chiral assembly is obtained by self-assembly of a gold thiol sheet and cyclohexanediamine; The following steps are involved: S1. Providing a two-dimensional chiral nanoassembly; The sodium salt of 3-mercaptopropionic acid is added to a boiling mixed aqueous solution of chloroauric acid and alkali solution, and a colloidal solution of gold (I)-mercaptopropionic acid two-dimensional nanoassemblies is obtained by a solvothermal synthesis method; the colloidal solution is post-treated to obtain a gold thiol two-dimensional nanoassembly solution; S2. providing an aqueous solution of a chiral two-dimensional nanoassembly; The gold mercaptan two-dimensional nanoassembly solution is added into the cyclohexanediamine aqueous solution and mixed to obtain a chiral two-dimensional nanoassembly aqueous solution through self-assembly; S3. Preparation of circularly polarized luminescent quantum dot materials; The circularly polarized luminescent quantum dot material is obtained by mixing the chiral two-dimensional nanoassembly aqueous solution and the quantum dot aqueous solution.

5. The preparation method according to claim 4, characterized in that: In S1, the reaction time of the solvent thermal synthesis method is 5 to 20 minutes; The alkali solution is a sodium hydroxide solution; The molar ratio of chloroauric acid to 3-mercaptopropionic acid monosodium salt is 1:3 to 1:5; The post-treatment includes centrifugation and purification; the centrifugation includes centrifugation at a speed of 8000 r / s for 10-20 minutes; The concentration range of the gold thiol two-dimensional nanoassembly solution is .

6. The preparation method according to claim 4, characterized in that: In S2, the concentrations of cyclohexanediamine in the aqueous solution of the chiral two-dimensional nanoassembly are ; The concentration of the chiral two-dimensional nanoassembly is M.

7. The preparation method according to claim 4, characterized in that: In S3, the concentration of the quantum dot aqueous solution is 0.13 mg / mL to 0.60 mg / mL; In the circularly polarized luminescent quantum dot material, the added volume ratio of the chiral two-dimensional nanoassembly and the quantum dots is 1:1.

Citation Information

Patent Citations

  • Circularly polarized luminescent material and preparation method thereof

    CN115505149A

  • Molybdenum disulfide quantum dot-chiral gold nano particle assembly as well as preparation method and application thereof

    CN112143494A

  • Room-temperature circularly polarized phosphorescent material based on carbon quantum dot-nucleobase derivative and preparation method thereof

    CN116463120A

  • Near-infrared circularly polarized luminescent material with ultra-wideband response and preparation method of near-infrared circularly polarized luminescent material

    CN118085868A